Behavior of Tunisian Local Barley Accessions Under Progressive Water Deficit: Physiological and Biochemical Approaches - R.Chaabane2,M.B.Naceur2,M.El Faleh2,C.Abdelli3,D.Ramla4,A.Nada5,M.Sakr6,J.B.Hmida7, Raoudha Abdellaoui1*, Mohamed Tarhouni1 (Journal of Phytology, 2011)
Leaf water potential, percentage of membrane integrity and pigments chlorophyll content provide information on plant water status, on cell membranes integrity and on its photosynthetic capacity particularly under water stress conditions. These parameters were used to differentiate the behavior of 14 local barley accessions subjected to various intensities of stress (one week, two weeks and three weeks). The Principal Component Analysis (PCA) of the collected data at the end of each week revealed that the accessions behavior varies with the water deficit period. In fact, some are tolerant during the first and/or second week of stress and subsequently they are affected with a very substantial reduction in their chlorophyll pigments and their percentage of membrane integrity after three weeks. Others appear to be sensitive during the first week of stress and became tolerant under severe stress. This tolerance is manifested by the maintenance of membrane integrity, high content of chlorophyll pigments, significant proline accumulation and important specific activity of peroxidases. The study also showed that the 14 accessions exhibit two behavior types: i) significant decrease in leaf water potential with proline accumulation (constitutive osmotic adjustment) to keep cells turgid and ii) trivial drop of leaf water potential (osmotic adjustment of adaptive type). Moreover, variability in the different accessions behavior to water deficit seems to be linked to their geographical origin especially that supposed tolerant accessions are mostly from South and Central Tunisia characterized by severe aridity. Key words: Barley; water stress; behavior; accessions; Tunisia <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Raoudha Abdellaoui et al. Behavior of Tunisian Local Barley Accessions Under Progressive Water Deficit: Physiological and Biochemical Approaches. J Phytol 2/11 (2010) 88-97.